Morphological description of early zoeal stages of Alpheus brasileiro Anker, 2012 reared in the laboratory, including a revision of the larval morphology of the first zoeal stage of the genus Alpheus Fabricius, 1798 (Caridea: Alpheidae) - Pescinelli, Régis A. [UNESP]; Pantaleão, João A. F. [UNESP]; Mantelatto, Fernando L.; Costa, Rogério C. [UNESP] (Magnolia Press, 2017)
The aims of this study were to describe and illustrate the early larval stages of the snapping shrimp Alpheus brasileiro Anker, 2012 and to review the larval morphology (Zoea I) of the genus Alpheus Fabricius, 1798. Larvae were obtained from two females with embryos collected in an intertidal estuary in Cananéia, São Paulo state, Brazil. The published descriptions of all available Alpheus zoea I (only 14 spp., 4.7%) were used for a comparison of larval morphology. The zoeae I of Alpheus species are very similar, but A. brasileiro can be separated from the other studied species by the following set of characteristics: antennal scale 5-segmented with 11 plumose setae and 2 simple setae; coxal endite of maxillule with 3 simple setae and 2 sparsely plumose setae; and coxal endite of maxilla with 1 simple seta and 1 sparsely plumose seta. The description of early larval development of A. brasileiro indicates consistent characteristics, which, when analyzed along with other morphological, molecular, and biogeographical aspects, can help to elucidate the complex phylogenetic relationships between the species in the group. However, this is the first zoeal description of a member of Alpheus armillatus species complex and it therefore does not permit a comparison. Only with new additional descriptions we will be able to generate a clearer scenario in this field due the high similarity among the species.
Keywords: Decapoda; Intertidal; Larval development; Snapping shrimp; Species complex